2019
DOI: 10.1116/1.5094429
|View full text |Cite
|
Sign up to set email alerts
|

Role of ionization fraction on the surface roughness, density, and interface mixing of the films deposited by thermal evaporation, dc magnetron sputtering, and HiPIMS: An atomistic simulation

Abstract: We explore the effect of ionization fraction on the epitaxial growth of Cu film on Cu (111) substrate at room temperature. We compare thermal evaporation, dc magnetron sputtering (dcMS) and high power impulse magnetron sputtering (HiPIMS). Three deposition conditions i.e. fully neutral, 50 % ionized and 100 % ionized flux were considered as thermal evaporation, dcMS and HiPIMS, respectively, for ∼20000 adatoms. It is shown that higher ionization fraction of the deposition flux leads to smoother surfaces by two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 61 publications
(95 reference statements)
4
45
1
Order By: Relevance
“…Regarding HiPIMS deposition, MD simulations have indicated that both ionization fraction and substrate bias change the microstructure and film-substrate intermixing [10,14]. Hence, the variation of the film texture by bias voltage that has been observed experimentally [19,20,13] can be attributed to the change of wetting due to interface mixing.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Regarding HiPIMS deposition, MD simulations have indicated that both ionization fraction and substrate bias change the microstructure and film-substrate intermixing [10,14]. Hence, the variation of the film texture by bias voltage that has been observed experimentally [19,20,13] can be attributed to the change of wetting due to interface mixing.…”
Section: Introductionmentioning
confidence: 91%
“…Due to the high electron density the ionization mean free path of the sputtered species becomes shorter and the ionization probability increases and a significant fraction of the ions reaching the substrate are ions of the film-forming species. As a result HiPIMS deposition presents smoother [8,9,10], denser [11,10], and less defective [12,10] coatings, compared to dcMS deposition. Further, by applying a substrate bias, the bombarding energy of the ions of the film forming material can be tuned in order to achieve desired film properties such as the film texture and grain size [13,14].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations